The Effect of Magic Book to Increase Interest in Learning Mathematics of Primary School Students - Maulani, MaghfirohIzza; Putri, Ashma Nur Hanifah Heninda; Faddliyah; Muslimah, Afifatul; Pangestu, Aji (Proceeding International Conference on Science and Engineering, 2020)
Elementary School is a place to understand all learning for the next level, especially mathematics. Mathematics is also considered difficult by elementary school students because of its abstract and complex nature, especially with the large number of mathematical formulas, and its lack of interest in learning. So that student interest in learning is reduced. One interesting way to learn mathematics is by using learning media. This research introduces MagicBook contains a collection of formulas and mathematical games. This Magicbook is arranged in such a way with an attractive layout and color. Sources of data obtained from questionnaires and direct research on elementary school students in one of the lessons in Yogyakarta. The data of this study were analyzed descriptively quantitative and qualitative. The results showed that the magic book learning media can increase elementary school students' mathematics learning interest.the effect.